A study of neurological functions in construction work painters - Lavanya Sekhar; Vidhya Venugopal; Santhanam R; Priscilla Johnson (Elsevier, 2024)
Background: Painters are constantly exposed to organic solvents containing volatile organic compounds (VOCs), a primary source of indoor air pollution. Prolonged exposure to solvents generates significant health repercussions on pulmonary and neurological functioning. Few studies have assessed the neurological function of unorganized sector painters objectively, especially in developing nations. The current research evaluates the effects of organic solvents on neurological functions in painters working in unorganized sectors like construction sites in Chennai. Methods: A validated questionnaire was used to assess solvent-exposed neurological symptoms in full-time painters (n = 75) aged 25-55, stratified by years of exposure (≤10 years, >10 years). A subset of 35 painters underwent bilateral median nerve motor and sensory nerve conduction studies. Personal exposure monitors measured VOC concentration during the painting processes. Results: Toluene and benzene concentrations were greater in paint scraping. 47% of painters reported neurological symptoms, and those with >10 years of experience had a higher AOR (95%CI): 3.4 (1.3, 9.6). 13% had diplopia, 18% had ocular discomfort. Painters with more than 10 years of experience had longer motor and sensory onset latency of the left median nerve, as well as decreased bilateral sensory conduction velocities (Right median nerve: 53.8 ± 13.9 vs 64.2 ± 5.2; Left median nerve: 55.75 ± 6.5 vs 64.3 ± 6.2). Conclusion: Paint emits toluene, a major solvent. The impact of occupational exposure to organic solvents on neurological functions has been observed to exhibit a progressive deterioration over time. Health awareness and strict protective measure legislation are needed to reduce morbidity and mortality in these unorganized sectors.